KONFLIK BATIN TOKOH UTAMA DALAM NOVEL SEGI TIGA KARYA SAPARDI DJOKO DAMONO - Adrianus Andika Richardo; Antonius Totok Priyadi; Christanto Syam (Universitas Tanjungpura, 2022)
This study aimed to describe the inner conflicts of the main character in the novel titled Segi Tiga by Sapardi Djoko Damono and its implemented at Indonesian language learning in junior high school. The method used is descriptive analytic with the form of qualitative research. The approach used is psychoanalysis. The research data source is in the form of the novel Segi Tiga text owned by Sapadri Djoko Damono published by PT Gramedia Pustaka Utama in 2020. The research data are quotations of words, phrases, sentences, and discourses. Data analysis uses reduction, display data, and verification. The results of this research show that there is an approach-approach conflict in the form of confusion, doubt and indecision. Avoidance conflict is in the form of anxiety, contradiction, depression, and expressions of anger. Approach avoidance conflict is conflict, surrender, hurt, disappointment, resentment, and jealousy. The factors that caused inner conflict are: differences between individuals with differences in opinion, differences in opinion, and differences in feelings; conflicting interests in the form of differences of interest; actual causes (precipitating causes) in the form of disability, disappointment, and anxiety; cultural differences in the form of cultural differences in choosing a partner. The resolution of the inner conflict experienced by the main character is in the form of apathy, sublimation, rationalization, displacement, repression, and fantasy.